PVA@MGO สำหรับเป็นตัวดูดซับในการสกัดด้วยวัฏภาคของแข็งที่มีสมบัติแม่เหล็กเพื่อวิเคราะห์สารกำจัดศัตรูพืชกลุ่มออร์กาโนฟอสเฟต - ศุภิสรา เจริญวงศ์ไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Organophosphate pesticides (OPPs) are pesticides applied in fruit and vegetable which are acutely toxic to the nervous system. At present, magnetic solid-phase extraction (MSPE) is used for determination of OPPs in food and environmental sample. This project focused on the synthesis of polyvinyl alcohol coated magnetic graphene oxide (PVA@MGO) and used as sorbent in MSPE technique. First, graphene oxide (GO) was synthesized by Tour’s method. Then, magnetic graphene oxide (MGO) was prepared by coprecipitation of Fe3O4 on GO. Finally, polyvinyl alcohol (PVA) was coated on the MGO surface using an H-bond between the hydroxyl group of PVA and the carbonyl group of MGO. For each step, the characterization of the sorbent is completed by Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) techniques.